2020
DOI: 10.2147/ppa.s224496
|View full text |Cite
|
Sign up to set email alerts
|

<p>Side Effects, Self-Management Activities, and Adherence to Oral Anticancer Agents</p>

Abstract: Purpose: There are growing concerns about patients' adherence to oral anticancer agents (OAAs), and the need for patients to engage in self-management of OAA-related side effects. We assessed associations among adherence, severity of side effects, and effectiveness of self-management of side effects in patients taking capecitabine. Methods: Adherence to capecitabine at 6 weeks was measured by the Medication Event Monitoring System among 50 patients with gastrointestinal cancers. Severity of side effects relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Four studies, of which one was higher quality [21], explored the association between health literacy and oral medication adherence. Adherence to general medications [71], specific oral chemotherapy (capecitabine) [21], and to various anti-cancer medications, including hormonal and targeted treatments [51,66] was assessed. Higher health literacy was associated with higher levels of adherence in three studies of up to 100 participants [21,51,71].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Four studies, of which one was higher quality [21], explored the association between health literacy and oral medication adherence. Adherence to general medications [71], specific oral chemotherapy (capecitabine) [21], and to various anti-cancer medications, including hormonal and targeted treatments [51,66] was assessed. Higher health literacy was associated with higher levels of adherence in three studies of up to 100 participants [21,51,71].…”
Section: Plos Onementioning
confidence: 99%
“…Adherence to general medications [71], specific oral chemotherapy (capecitabine) [21], and to various anti-cancer medications, including hormonal and targeted treatments [51,66] was assessed. Higher health literacy was associated with higher levels of adherence in three studies of up to 100 participants [21,51,71]. One study of patients with gynaecological cancers (N = 100) did not report a significant association, though it was not powered to detect predictors of non-adherence [66].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Although the measurement of capecitabine self-management using the adopted Measure of Drug Self-Management [15] might not be comprehensive enough to cover all six steps from Fill to Sustain, this pilot study did reveal the association between capecitabine self-management and patient experiences with and concerns of side effects, as well as their perceived abilities to manage them. To understand patient side effect self-reporting behaviors, a post-study of the same cohort, researchers phone interviewed 36 patients [14]. The results indicated that twothirds of patients (n=24) had called their doctors or nurses regarding capecitabine treatment related problems.…”
Section: Resultsmentioning
confidence: 99%
“…EHR data from the remaining 47 patients were included in this combined data analysis. The pilot study was an observational, single-group study that collected patient-reported side effects through telephone calls from 50 adult patients who were diagnosed with gastrointestinal (GI) cancers and had taken capecitabine for at least two cycles [12]. The nal combined dataset consisted of 97 adult patients who were taking capecitabine in 2016-2017.…”
Section: Study Design and Samplementioning
confidence: 99%